The importance of hospital dentistry: oral health status in hospitalized patients - Cristhiane Olívia Ferreira do AMARAL; Letícia Marçal Ruthes BELON; Elza Aparecida da SILVA; Andressa de NADAI; Marcelo Sávio Paiva do AMARAL FILHO; Fabiana Gouveia STRAIOTO (Faculdade São Leopoldo Mandic, 2018)
Objective: This research study aimed to evaluate the oral health status and the need for dental treatment in hospitalized patients, analyzing the importance of dentistry in hospitals. Therefore, the goal of this research study was to evaluate the oral health status, the need for dental intervention and the patient's opinion about the importance of having dental surgeons in hospital settings. Methods: 103 hospitalized patients were evaluated considering the DMFT index, gingival condition, visible biofilm index, and the need for invasive dental treatment. Volunteers were also asked about their opinion considering the importance of dentistry in hospital settings. Results: 68.9% of volunteers were male subjects and 31.1% female subjects. The mean DMFT was 17.9 and 96.1% of subjects had their oral hygiene kit with when came to hospital, 97.1% of subjects stated that the presence of dental surgeons is necessary in the hospital setting and 63.1% of subjects presented poor biofilm removal. The need for invasive dental treatment was as follows: restorations (68.9%), extractions (40.8%), endodontics (23.3%), dental pain (26.2%) and presence of abscess (7,8%). Conclusion: Oral health and hygiene status of patients were classified as poor and most of patients showed the need for invasive dental treatment. The majority of patients reported that dental care is very important in hospitals settings.